A Deep Intronic Variant in LDLR in Familial Hypercholesterolemia: Time to Widen the Scope?. (December 2018) - Reeskamp, Laurens F.; Hartgers, Merel L.; Peter, Jorge; Dallinga-Thie, Geesje M.; Zuurbier, Linda; Defesche, Joep C.; Grefhorst, Aldo; Hovingh, G. Kees
Abstract : Background: Familial hypercholesterolemia (FH) is an inherited disorder characterized by high plasma LDL-C (low-density lipoprotein-cholesterol) levels. The vast majority of FH patients carry a mutation in the coding region of LDLR, APOB, or PCSK9 . We set out to identify the culprit genetic defect in a large family with clinical FH, in whom no mutations were identified in the coding regions of these FH genes. Methods: Whole genome sequencing was performed in 5 affected and 4 unaffected individuals from a family with an unexplained autosomal dominant FH trait. The effect on splicing of the identified novel intronic LDLR mutation was ascertained by cDNA sequencing. The prevalence of the novel variant was assessed in 1 245 FH patients without an FH causing mutation identified by Sanger sequencing and in 2 154 patients referred for FH analysis by next-generation sequencing (covering the intronic region). Results: A novel deep intronic variant in LDLR (c.2140+103G>T) was found to cosegregate with high LDL-C in 5 patients, but was not present in 4 unaffected family members. The variant was shown to result in a 97 nucleotides insertion leading to a frameshift and premature stop codon in exon 15 of LDLR . The prevalence of the intronic variant was 0.24% (3/1245) in a cohort of FH patients without a known FH causing mutation and 0.23% (5/2154) in a population of FH patients referred for analysis by next-generation sequencing. Cosegregation analysis of a second family showed full penetrance of the novel variant with the FH phenotype over 3 generations. Conclusions: The c.2140+103G>T mutation in LDLR is a novel intronic variant identified in FH that cosegregates with the FH phenotype. Our findings underline the need to analyze the intronic regions of LDLR in patients with FH, especially those in whom no mutation is found in the coding regions of LDLR, APOB, or PCSK9 . Abstract : Supplemental Digital Content is available in the text.